1993
DOI: 10.1029/92rs01931
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Errors in Radar Wind Estimation: Implications for Comparative Measurements

Abstract: SA, IDI, and DBS horizontal wind estimators are examined and demonstrated to share common biases under inhomogeneous flow field conditions. The biases can reach magnitudes of several tens of meters per second at mesospheric heights, contaminate gravity wave flow field measurements, cause distortions in measured flow field spectra, and possibly account for large wind measurement errors evidenced in recent experimental studies including the AIDA'89 effort. However, being a linear response to gravity wave flow fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…There has been much debate about the precise scattering mech-Previous studies of mesosphere winds measured using MF radars have highlighted discrepancies between the various techniques [e.g. Kudeki et al, 1993]. While such discrepancies are still under investigation, one of the fundamental issues is that the physical processes responsible for radar scatterring structures in the mesosphere are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much debate about the precise scattering mech-Previous studies of mesosphere winds measured using MF radars have highlighted discrepancies between the various techniques [e.g. Kudeki et al, 1993]. While such discrepancies are still under investigation, one of the fundamental issues is that the physical processes responsible for radar scatterring structures in the mesosphere are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of horizontal wind estimates by the horizontal gradient of the vertical wind [Royrvik, 1983;Kudeki et al, 1993] can cause an enhancement of the power spectral density (PSD) at high frequencies. In the 10-min to 2-hour band, the degree of this enhancement on the estimated variance is expected to be less than 20% [Rastogi et al, 1996].…”
Section: Observationsmentioning
confidence: 99%
“…The Hines et al (1993) results also motivated modeling studies by Kudeki et al (1993) and Surucu et al (1995). These studies suggested that MF/HF SA wind measurements were suitable for measurement periods longer than about 1 h. Hocking (1987) noted that wind measurements made over shorter time intervals were potentially usable, but some care needed to be exercised to recognize the potential contaminating effects of vertical velocities associated with short period gravity waves on the results.…”
Section: Aida 89 Campaignmentioning
confidence: 96%
“…Using a simple model, Reid (1987) demonstrated the limitations of Doppler radars with different beam geometries in measuring atmospheric parameters. Kudeki et al (1993) also considered the impact of inhomogeneous winds fields on SA, DBS, and IDI radar measurements using theoretical arguments and concluded that such inhomogeneity could led to significant biases in such measurements. Surucu et al (1995) extended the Kudeki et al (1993) model to include both isotropic and non-isotropic scatterers and concluded that the SA radars produced the horizontal wind as long as any waves present had horizontal scales larger than the horizontal scale of the SA radar pulse volume.…”
Section: Mf/hf Meteor Radarsmentioning
confidence: 99%
See 1 more Smart Citation